Etanercept treatment for extended oligoarticular juvenile idiopathic arthritis, enthesitis-related arthritis, or psoriatic arthritis: 6-year efficacy and safety data from an open-label trial - Foeldvari, Ivan; Constantin, Tamàs; Vojinović, Jelena; Horneff, Gerd; Chasnyk, Vyacheslav; Dehoorne, Joke; Panaviene, Violeta; Sušić, Gordana; Stanevicha, Valda; Kobusinska, Katarzyna; Zuber, Zbigniew; Dobrzyniecka, Bogna; et al. (Arthritis research & therapy, 2019)
BACKGROUND: To describe the 6-year safety and efficacy of etanercept (ETN) in children with extended oligoarticular juvenile idiopathic arthritis (eoJIA), enthesitis-related arthritis (ERA), and psoriatic arthritis (PsA) METHODS: Patients who completed the 2-year, open-label, phase III CLinical Study In Pediatric Patients of Etanercept for Treatment of ERA, PsA, and Extended Oligoarthritis (CLIPPER) were allowed to enroll in its 8-year long-term extension (CLIPPER2). Children received ETN at a once-weekly dose of 0.8 mg/kg, up to a maximum dose of 50 mg/week. Efficacy assessments included the JIA core set of outcomes, the JIA American College of Rheumatology response criteria (JIA-ACR), and the Juvenile Arthritis Disease Activity Score (JADAS). Efficacy data are reported as responder analyses using a hybrid method for missing data imputation and as observed cases. Safety assessments included treatment-emergent adverse events (TEAEs). RESULTS: Out of 127 patients originally enrolled in CLIPPER, 109 (86%) entered CLIPPER2. After 6 years of trial participation (2 years in CLIPPER and 4 years in CLIPPER2), 41 (32%) patients were still taking ETN, 13 (11%) entered the treatment withdrawal phase after achieving low/inactive disease (of whom 7 had to restart ETN), 36 (28%) discontinued treatment for other reasons but are still being observed, and 37 (29%) discontinued treatment permanently. According to the hybrid imputation analysis, proportions of patients achieving JIA ACR90, JIA ACR100, and JADAS inactive disease after the initial 2 years of treatment were 58%, 48%, and 32%, respectively. After the additional 4 years, those proportions in patients who remained in the trial were 46%, 35%, and 24%. Most frequently reported TEAEs [n (%), events per 100 patient-years] were headache [28 (22%), 5.3], arthralgia [24 (19%), 4.6], and pyrexia [20 (16%), 3.8]. Number and frequency of TEAEs, excluding infections and injection site reactions, decreased over the 6-year period from 193 and 173.8, respectively, during year 1 to 37 and 61.3 during year 6. A single case of malignancy (Hodgkin's lymphoma) and no cases of active tuberculosis, demyelinating disorders, or deaths were reported. CONCLUSIONS: Open-label etanercept treatment for up to 6 years was safe, well tolerated, and effective in patients with eoJIA, ERA, and PsA. TRIAL REGISTRATION: ClinicalTrials.gov: CLIPPER, NCT00962741 , registered 20 August, 2009, CLIPPER2, NCT01421069 , registered 22 August, 2011.
Keywords: Psoriatic arthritis (PsA); Efficacy; Humans; Etanercept; dítě; Clinical trial; Child; antirevmatika; Female; etanercept; výsledek terapie; lidé; Enthesitis-related arthritis (ERA); Juvenile idiopathic arthritis; předškolní dítě; juvenilní artritida; ženské pohlaví; Male; Arthritis, Juvenile; Adolescent; Treatment Outcome; Extended oligoarticular juvenile idiopathic arthritis (eoJIA); Safety; mužské pohlaví; Child, Preschool; Antirheumatic Agents; Enthesitis-related arthritis; mladiství